IMPLEMENTATION OF ISO 9001 STANDARD IN INCREASING THE QUALITY OF COLLEGE STUDENTS - Steven Johny Runtuwene; Fitria Claudya Lahinta; Maya Munaiseche; Charistia Mengerongkonda; Jackson Ngosa; Ridel Rompas; Ernesto Medau; Anatasya Lumeta; Stefanus Angkow (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
ISO 9001 is one of the most recognized international standards used in the quality management field of work. The standard provides guidelines for developing, implementing, and maintaining an effective Quality Management system, or QMS, within the organization. This journal will discuss implementing the ISO 9001 standard at Politeknik Negeri Manado and the impact on improving the product, in this case, the quality of college students and their service quality. The purpose of this journal is to see if Politeknik Negeri Manado has reached the ISO 9001 Standard or not. The result examined that implementation of ISO 9001 is very effective in improving the quality of students that the campus produces and that many campuses in Manado should implement this standard in their campus so that the students will be more than capable of handling the work environment rather than just having the knowledge but not being qualified to handle the work